Adherence to Dihydroartemisinin-Piperaquine Treatment among Patients with Uncomplicated Malaria in Northern Ghana. (1st April 2019) - Oduro, Abraham Rexford; Chatio, Samuel; Beeri, Paula; Anyorigiya, Thomas; Baiden, Rita; Adongo, Philip; Akweongo, Patricia
Abstract : Treatment adherence has been described as the process whereby patients take medications, follow diet, and effect other lifestyle changes that relate to agreed recommendations from healthcare providers. The determinants of such treatment adherence include patient, the health condition, therapy type, socioeconomic conditions, and the healthcare system. The study examined adherence in malaria patients treated with dihydroartemisinin-piperaquine in routine clinical care in northern Ghana. The study was conducted in Navrongo Health Research Centre in the Kassena-Nankana district of northern Ghana. Patients confirmed with uncomplicated malaria were prescribed dihydroartemisinin-piperaquine in blister packs to be taken daily for three days. Follow-up visits were made on days 3 and 28 after diagnosis to collect data on adherence, drug safety and therapeutic effectiveness. During follow-up visits, in-depth interviews were conducted and the blister packs directly observed for the number of tablets remaining. The in-depth interviews documented day-by-day account of doses taken, number of tablets taken during each dose, time of each dose, reasons for any leftover or missed dose, and whether or not there was vomiting. Treatment adherence was classified as definitely nonadherent, incomplete adherence, and completely adherent. A total of 405 patients were screened; 299 were positive by rapid diagnostic testing and 216 by microscopy. The average age was 12 years and females represented 54.0%. All participants completed day 3 follow-up but 12.7% had leftover pills. Treatment adherence was 50.9% (95% CI 44.1, 57.8), 36.1% (95% CI 29.7, 42.9), and 13.0% (95% CI 8.8, 18.2) for completely adherent, incomplete adherence, and definitely nonadherent, respectively. All completely adherent patients were free of parasitemia on day 28 of follow-up. A total of 49 adverse events related to malaria symptoms were documented. Effort to improve adherence should be individualized as it is dependent on a number of factors such as the patients' temperament, the disease, support at home, and complexity of treatment.